New Singular and Nonsingular Colliding Wave Solutions in Einstein - Maxwell - Scalar Theory - Gürtuğ, Özay; Halilsoy, Mustafa; Sakallı, İzzet (General Relativity and Gravitation, 2003)
A technique is given to generate coupled scalar field solutions in colliding Einstein - Maxwell (EM) waves. By employing the Bell - Szekeres solution as seed and depending on the chosen scalar field it is possible to construct nonsingular solutions. If the original EM solution is already singular addition of scalar fields does not make the physics any better. In particular, scalar field solution that is transformable to spherical symmetry is plagued with singularities.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.1023/A:1027349606694) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: general relativity; Colliding Wave Solution